Photo-elicitation as a Method of Assessing Village Needs - Lulu Rodriguez; Denise Bjelland (Journal of Applied Communications, 2008)
Photo-elicitation is a method of gathering data from respondents who are asked to take photographs or critically examine and reflect on images taken by others to offer a more “native” view of often cross-cultural or inter-group experiences. This method was applied to determine what the residents of a village in China’s Hangzhou province saw as their community’s development priorities by asking them to take photographs of local scenes, characters and objects to depict their needs. Through their snapshots, they indicated the need to diversify their community’s economic base (currently limited to snake production and processing), the need for better transportation and for more markets for their products. On the other hand, the faculty and students of a university mandated to develop an extension force to serve the village’s agricultural needs indicated in a focus group that their rural clients were likely to clamor for more markets, lenient government policies, and educational opportunities. Examples of studies that have used this approach and the strengths and limitations of the photo-elicitation technique to assess village needs for extension planning are discussed.
Keywords: Photo-elicitation; China’s Hangzhou province; communication; practitioners; ethnographers; anthropologists